2020
DOI: 10.3390/ijms21030879
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immune Checkpoint Blockade in Uveal Melanoma

Abstract: Uveal melanoma (UM) represents the most common intraocular malignancy in adults and accounts for about 5% of all melanomas. Primary disease can be effectively controlled by several local therapy options, but UM has a high potential for metastatic spread, especially to the liver. Despite its clinical and genetic heterogeneity, therapy of metastatic UM has largely been adopted from cutaneous melanoma (CM) with discouraging results until now. The introduction of antibodies targeting CTLA-4 and PD-1 for immune che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 187 publications
(237 reference statements)
2
63
0
3
Order By: Relevance
“…More and more clinical data show that cancer immunotherapy is a key step in clinical cancer treatment [19,20]. Cancer management methods, especially non-small cell lung cancer, melanoma, urothelial cancer, and kidney cancer, and some preclinical and clinical trials have confirmed that immunotherapy has achieved encouraging results in many malignancies, including pancreatic cancer [21][22][23]. However, based on available data, it is clear that ICB has limited success in pancreatic cancer, which is also related to the low immunogenicity and immunosuppressive tumor microenvironment of pancreatic cancer [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…More and more clinical data show that cancer immunotherapy is a key step in clinical cancer treatment [19,20]. Cancer management methods, especially non-small cell lung cancer, melanoma, urothelial cancer, and kidney cancer, and some preclinical and clinical trials have confirmed that immunotherapy has achieved encouraging results in many malignancies, including pancreatic cancer [21][22][23]. However, based on available data, it is clear that ICB has limited success in pancreatic cancer, which is also related to the low immunogenicity and immunosuppressive tumor microenvironment of pancreatic cancer [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…More and more clinical data show that cancer immunotherapy is a key step in clinical cancer treatment 18,19 . Cancer management methods, especially non-small cell lung cancer, melanoma, urothelial cancer, and kidney cancer, and some preclinical and clinical trials have con rmed that immunotherapy has achieved encouraging results in many malignancies, including pancreatic cancer [20][21][22] . However, based on available data, it is clear that ICB has limited success in pancreatic cancer, which is also related to the low immunogenicity and immunosuppressive tumor microenvironment of pancreatic cancer 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Ein anderer Ansatz beinhaltete die Kombination von PD-L1-CD80-Heterodimerisierung und Suppression der CTLA-4/CD80-Achse [17]. Gegenwärtig werden die Antikörper Ipilimumab und Tremelimumab gegen CTLA-4 eingesetzt, während Nivolumab, Pembrolizumab und Cemiplimab für das Targeting von PD-1 und Atezolizumab und Avelumab gegen PD-L1 zur Anwendung kommen [14, 18, 19].…”
Section: Einführungunclassified